Analisis Penambahan Sarana Penunjang Kegiatan LRT Untuk Kemudahan Mobilitas Masyarakat Di Wilayah Palembang - Putri, Nur Huluwah Asadillah; Sahara, Siti (Sahabat Publikasi, 2023)
Addition of supporting facilities for Light Rail Transit (LRT) activities to increase ease of community mobility in the Palembang area. Considering population growth and the need for efficient transportation, this research focuses on evaluating the potential benefits of improving LRT supporting infrastructure, such as stations, parking and other facilities. Efforts to increase service occupancy through the implementation of subscription cards, and the development of park and ride to improve Palembang City LRT transportation services. It is hoped that the research results will provide a comprehensive view regarding the needs for LRT supporting infrastructure and provide recommendations for improving the transportation system to improve the quality of life of the community. It is hoped that the implications of this research will be the basis for decision making regarding the development of LRT and supporting infrastructure in the Palembang area.